Pengaruh Pembelajaran Kewirausahaan dan Perencanaan Karir terhadap Niat Berwirausaha pada Mahasiswa - Elvira Maulika; Habibullah Jimad; Mirwan Karim (Goodwood Publishing, 2022)
The trend of increasing educated unemployed people is an indication of low entrepreneurial interest. From the demand, the unemployment rate is related to the number of job opportunities available in the global era. Meanwhile, from the supply, the unemployment rate is a number of qualified workers in Indonesia. Responding today and future business world competition which relies more on knowledge and intellectual capital, in order to become the nation's competitiveness, development of young entrepreneurs needs to be directed at a group of educated (intellectual) people, namely students. Entrepreneurship education has been developed in almost all universities in Indonesia with very varied process at creating entrepreneurship. This study took a population of all students at the Unila with sample of 154 respondents. This research is included the research design of a causal study that proves a causal or relationship's influenced and affects between entrepreneurial learning, career planning and entrepreneurial interests. results of this study indicate that entrepreneurship learning methods that are applied effectively in the university environment can affect students' interest in entrepreneurship. This study also shows the existence of good career planning can affect student interest in entrepreneurship. Therefore, good entrepreneurship learning and career planning are needed to entrepreneurial intentions.